Analyzing the Reality of Iraq's Investment Environment and Measuring the Impact of Foreign Direct Investment on Unemployment Rates for the Period (2005-2020) - عبد على, خالد حيدر; قادر سليمان, باخان (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
The investment and its income, is one of the important sources of financing the economic activities necessary for the process of economic development. Where the investment is launched directly through an investment environment based on its various dimensions (political, legal, social ,etc.) suitable for the settlement of local investment, attracting foreign investment and adopting a favorable investment policy. It could lead to securing job opportunities to employ the increasing numbers of the unemployed (reducing unemployment.( This research aims to clarify the reality of the investment environment in Iraq and the impact of foreign direct investment on unemployment rates in Iraq for the period 2005-2020 and the use of Co-integration test (Johannsen) Causality Tests (Granger), use of the (OLS) model, The research concluded that the investment environment in Iraq is unstable, due to the instability of its political, security and legal situation, in addition to the presence of administrative and financial corruption rampant in various government agencies. Despite this, there was a relative stability in the macroeconomic variables, as well as the existence of a direct relationship between foreign direct investment and the unemployment rate. This indicates that the more foreign direct investment increases, unemployment rates also increase. Because most foreign investments are characterized by capital intensity and lack of work, and in addition to that, foreign labor is brought in (within the aforementioned investment), which operates with less income than the local labor force, and this has increased unemployment rates Accordingly, the research emphasized the need to find an appropriate investment environment that works to attract foreign investment that is heavily used for the labor element to contribute (albeit relatively) to addressing the problem of unemployment in Iraq.